Protection of mild steel from corrosion in an aggressive chloride media through chitosan-CeO2 nanocomposite: Experimental and computational studies - Himanshi Bairagi; Priya Vashishth; Rajni Narang; Sudhish K. Shukla; Bindu Mangla (Corrosion Communications, 2024)
In this study, synthesis of cerium dioxide nanoparticles (CeO2 NPs) and preparation of chitosan-CeO2 nanocomposite (CH-CeO2 NC) were done and examined their inhibitive nature on mild steel surface in 1 mol/L HCl solution. Characterization was done through ultraviolet-visible (UV–Vis) and Fourier transform infrared (FT-IR) spectroscopy. Mass loss, electrochemical studies were used to determine the anticorrosive parameters of the prepared materials. Morphology, composition, and size were evaluated with scanning electron microscopy/energy dispersive spectrometry and X-ray diffraction. The inhibition efficiency was increased from 76.9% to 98.9% with the introduction of NPs in the CH. Atomic force microscopy and density functional theory results are in compliance with experimental studies and confirm the better performance of CH-CeO2 NC over chitosan.